Combining Individual Phenotypes of Feed Intake With Genomic Data to Improve Feed Efficiency in Sea Bass - Besson, Mathieu; Allal, François; Chatain, Béatrice; Vergnet, Alain; Clota, Frédéric; Vandeputte, Marc (Frontiers in Genetics, 2019)
Measuring individual feed intake of fish in farms is complex and precludes direct selective breeding for feed conversion ratio (FCR). Here, we estimated the individual FCR of 588 sea bass using individual rearing under restricted feeding. These fish were also phenotyped for their weight loss at fasting and muscle fat content as possible indirect indicators of FCR. The 588 fish were from a full factorial mating between parental lines divergently selected for high (F+) or low (F-) weight loss at fasting. The pedigree was known back to the great grandparents. A subset of 400 offspring and their ancestors were genotyped for 1,110 SNPs, which allowed estimating the genomic heritability of traits. Individual FCR and growth rate in aquarium were both heritable (genomic h² = 0.47 and 0.76, respectively) and strongly genetically correlated (-0.98), meaning that under restricted feeding, faster growing fish were more efficient. FCR in aquariums was significantly better for fish with two F- parents (1.38), worse for fish with two F+ parents (1.51) and intermediate (1.46) for crossbred fish (F+/F- or F-/F+). Muscle fat content was positively genetically correlated to growth rate in aquarium and during fasting. Thus, higher growth rate in aquariums, lower weight loss at fasting and fat content are all traits that could improve FCR in aquarium. Improving these traits would also improve FCR of fish in normal group rearing conditions, as we showed that groups composed of fish with good individual FCR were significantly more efficient in groups. The FCR of groups was also better when the fish composing the groups had, on average, lower estimated breeding values for growth rate during fasting (losing less weight). Thus, FCR in aquarium and weight loss at fasting are both promising to improve FCR of fish in groups. Finally, we showed that the reliability of estimated breeding values was higher (from +10% to +125%) with single-step genomic BLUP than with pedigree-based BLUP, showing that genomic data would enhance the accuracy of EBV prediction o in selection candidates from a limited number of sibs individually phenotyped for FCR in aquariums.